Ion Implantation in the Form of Layers: A Novel Method to Surface Properties - Shafique, Muhammad Ahsan; Zaheer, Z.; Sharif, S.; Taskeen, H.; Shah, S. A.; Akhtar, Athar Naeem; Murtaza, G.; Farid, Ghulam; Farid, Ghulam (Journal of Materials and Physical Sciences, 2022)
In this study, a novel method was adopted to tailor the surface properties of iron. We attempted to increase the degradation rate of iron by H-induced damaging. Equal number of H ions were implanted in four samples using a 2MV Pelletron accelerator. But the ion distribution was varied in the iron matrix by adding H ion layers in successively increasing depths. Interesting outcomes, contrary to our assumption were observed. The open-circuit potential was observed to shift toward a stable side. The Tefal plot also revealed improved corrosion potential and decreased corrosion current by adding H layers. Crystallographic studies revealed improved crystallinity and a small shift in preferred orientation of crystal growth.